A NEED ANALYSIS OF ENGLISH LEARNING FOR DESIGNING ENGLISH CURRICULUM AND WORKSHEET ( A Case Study for the sixth semester of Electrical Engineering Students in the Academic Year of 2015/2016 at State Polytechnic of Cilacap) - Betti Widianingsih; Rostika Listyaningrum (Epigram, 2019)
AbstractThe purpose of english learning in higher education level is used as mean to develop the competence of language skill which includes listening, speaking, reading, and writing. English is one of basic course which being compulsory course followed by students. The way of english learning for engineering students differs from english learning for english department students. ESP is an english learning with specific purposes. It aims to make students able to master english skill based on their discipline. It is designed to prepare english learners in specific job and discipline for reaching specific goals. Therefore, this research aims to find out and describe student’s need for english learning, and also explain the importance of english in a workplace in the field of engineering. The research involved the sixth semester of Electrical Engineering students in the academic year 2015/2016, lectures in Electrical engineering department at State Polytechnic of Cilacap and stakeholders. The method of collecting data used questionnaire and direct interview. The finding of the research is becoming a reference to create the syllabus design or development of worksheet for ESP. From the research, it can be clearly concluded that english learning should be focused on the language skill and also adjusted to the student’s need for electrical engineering and preparation to work.Key words : need analysis, ESP, english learning, electrical engineering studentAbstrakDi tingkat perguruan tinggi, tujuan pembelajaran bahasa Inggris digunakan sebagai sarana mengembangkan kompetensi keterampilan berbahasa mahasiswa yang mencakup mendengarkan, berbicara, membaca, dan menulis. Bahasa Inggris merupakan Mata Kuliah Dasar Umum yang menjadi mata kuliah wajib yang diajarkan. Sebagai Mata Kuliah Dasar Umum pada non program studi bahasa Inggris, arah pembelajaran bahasa Inggris untuk non program studi bahasa Inggris berbeda dengan bahasa Inggris pada program studi bahasa Inggris. English for Specific Purposes (ESP) adalah bahasa Inggris untuk tujuan khusus. ESP bertujuan agar pembelajar mampu menguasai bahasa Inggris pada bidang yang mereka pelajari dan biasa dikenal sebagai mata kuliah Bahasa Inggris bagi mahasiswa non program studi bahasa Inggris. ESP didesain untuk menyiapkan pembelajar bahasa Inggris yang digunakan dalam disiplin ilmu dan pekerjaan tertentu demi mencapai tujuan tertentu. Oleh karena itu, penelitian ini bertujuan untuk menemukan dan mendeskripsikan kebutuhan terhadap pembelajaran ESP pada mahasiswa dan pentingnya peranan bahasa Inggris pada dunia kerja dalam bidang keteknikan. Penelitian ini melibatkan mahasiswa semester enam tahun ajaran 2015/2016, Dosen Program studi Teknik Elektronika Politeknik Negeri Cilacap, dan juga stakeholders. Teknik pengumpulan data yang digunakan adalah kuesioner dan melakukan wawancara langsung. Hasil penelitian ini akan digunakan sebagai acuan untuk membuat silabus maupun pengembangan materi atau bahan ajar untuk bahasa Inggris ESP. Dari hasil penelitian dapat ditarik kesimpulan bahwa pengajaran bahasa lebih difokuskan pada keterampilan bahasa, topik bahan ajar dipilih sesuai dengan disiplin ilmu dan kebutuhan di dunia kerja.Kata Kunci : analisis kebutuhan , ESP, pembelajaran bahasa inggris, mahasisa teknik elektronika